Disparity in Perceptions of Social Values for Ecosystem Services of Urban Green Space: A Case Study in the East Lake Scenic Area, Wuhan - Chen, Yuanyuan; Ke, Xinli; Min, Min; Cheng, Peng (Frontiers in Public Health, 2020)
Abstract: Urban green space can bring various kinds of ecosystem benefits to diverse social groups. Among all of those ecosystem benefits, intangible social values are often neglected but highly relevant to the welfare of human beings. Existed researches on social values of urban green space often focused on the perspective of urban inhabitants and instead of tourists who are also one of the main beneficiaries. With combining different data sources to deliver a comprehensive knowledge of social values for green space, this paper tried to investigate the perception disparity of inhabitants and tourists about spatial pattern of social values in the East Lake scenic spots, Wuhan, and it also further explored the underlying environmental influential factors of the perceptual differences. For this, we collected 347 questionnaires through on-site survey and 11,908 photos uploaded by 2165 users from social media (Sina Blog), and we applied SolVES (Social Value for Ecosystem Services) to manifest the spatial pattern of social values and relationship among social value indicators and natural surroundings. The results showed that hot spots of social values, locating nearly to water and trails, scattered the whole scenic area. Nevertheless, perceptual disparity existed between inhabitants and tourists. Compared to tourists, inhabitants perceived larger scale of social values and could benefit more from recreation and economic values. Whereas, aesthetic and cultural values were appreciated higher for tourists. Underlying environmental conditions contributed to the anticipation of social values at different extent, noteworthily, distance to water and land cover exerted significantly influence. These findings should be taken into consideration to improve urban spatial development planning and optimize the green infrastructures to maximize human welfare.Chen et al.